Descriptive and Psychometric Properties of the Inventory of Motivations for Suicide Attempts (IMSA) in an Inpatient Adolescent Sample. Issue 3 (2nd July 2016) - May, Alexis M.; O'Brien, Kimberly H. McManama; Liu, Richard T.; Klonsky, E. David
Abstract : Little is known about why adolescents attempt suicide. The current study examined the endorsement, structure, and clinical correlates of adolescents' suicide attempt motivations as measured by the Inventory of Motivations for Suicide Attempts (IMSA). Suicidal adolescents (n = 52) in a psychiatric unit were administered the IMSA and interviewed about their suicide attempts. Psychache, Hopelessness, and Escape were the most strongly endorsed motivations, and Interpersonal Influence the least endorsed. IMSA scales exhibited a 2-factor solution: 1) Internal and 2) Communication. Suicide intent was strongly correlated with Internal motivations and moderately inversely correlated with Communication motivations. Factor structure and mean endorsements were similar to adult samples. The IMSA is a useful measure to assess attempt motivations in adolescents.